Effect of Glass Ceiling on Women’s Career Development in Nepalese Commercial Banks - Bhandari, Dilli Ram; Subedi, Dhruba Prasad (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
Eliminating gender prejudice in job advancement is not only crucial for promoting fairness and equality but also essential for maximizing organizational success. The primary objective of this study is to explore the glass ceiling factors that hinder the career growth of women employees in Nepalese commercial banks. To achieve the research objective, the data were collected from the primary source mainly through structured questionnaire and group discussion method under random sampling technique. An exploratory research design was followed to explore the factors that restrict the career development of women employees in Nepalese commercial banks. Merely this study has been completed with an empirical survey which was thoroughly conducted using a self-administered questionnaire and group discussion and the sample consisted of 280 middle-level women executives. For presenting and analyzing the data both descriptive and inferential statistics were used. The study revealed that Nepalese women workers do not face much career related problems. The organizations perceive that women are as capable as males in discharging their responsibilities. However, there are some assignments in which women are under rated than males in dealing with some unique situations. Likewise, some cultural issues, management and family perceptions are likely to hinder the performance and enthusiasm of the women toward their career advancement.